Byzantine Wall Paintings and Icons at Meteora - Vapheiades, Konstantinos M. (Actual Problems of Theory and History of Art, 2023)
Τhe region of Meteora, West Thessaly, is not only one of the most important centres of Christian spirituality, but a preeminent ark of medieval art and European culture as well. The paper provides an overview of a central aspect of this heritage: the decoration of churches with wall paintings and icons. Despite the significant ensembles and remnants surviving in the vicinity of Meteora, a comprehensive art historical assessment of these monuments remains a desideratum, especially considering our limited knowledge on workshops, exact dates and patrons. Nevertheless, these venerated works of art are of prime importance mainly because of their association with artistic tendencies which emanate from Constantinople, Thessaloniki, and in some cases even Italy. Thus, by examining the mentioned painting ensembles, this paper provides a clear outline of the succession of artistic tendencies in visual production at Meteora throughout the Byzantine period.
Keywords: Thessaly; Stagoi; Meteora monasteries; Great Meteoron Monastery; St. Athanasios of Meteora; Symeon Uroš Palaiologos; Byzantine wall paintings; Byzantine icons